Analysis of Receivable Planning and Supervision at PT. Wicaksana Overseas International Tbk Sumatera 1 - Novien Rialdy (AIBPM Publisher, 2021)
Accounts receivable of a company is generally one of the largest assets of current assets and the largest part of total assets. In managing financial management, especially regarding accounts receivable, it is necessary to plan and analyze carefully, so that trade receivables management policies can run effectively and efficiently, both regarding receivables procedures, receivable collection, credit sales and other receivable problems. This research approach uses a descriptive approach. The type of data collected to support the research variables is qualitative data and the data source used is secondary data. Data collection technique in this research is documentation technique. The data analysis technique used by the author is descriptive method. Based on the results of research with accounting control procedures that have been set by PT. Wicaksana Overseas International, Tbk has been implemented well, but physical supervision has not been implemented properly. The company has not been able to fully collect the company's short-term receivables from other collaborating companies. This can be seen from the unplanned and well controlled billing process carried out by the company. planning can play a more important role than other management functions, because organizing, directing and controlling actually carry out the decisions made in planning.